Kushth A Chronic Skin Disorder- Literary Review - Trivedi, Diksha; Gupta, Rajesh (International Research Journal of Ayurveda & Yoga, 2020)
In ancient Ayurveda, skin disorders are vastly described under ‘kushth rog’. Generally, it is also called twak dosha and kushth rog is further divide into two categories e.g. mahakushth and kshudra kushth. It is mentioned that due to pitta pradoshaj vikar and rakt pradoshaj vikar, skin diseases arise. Some acharya considered it as result of sin deeds as well. Acharya Charak, has described it as a rakt pradoshaj vikar and Sushruta has described it as an ‘Aupsargik Vyadhi’. In our classical texts there is clearly mentioned the etio pathogenesis like sapta dravyas, vata, pitta, kapha, twacha, rakta, ambu/ lasika, mansa they all together manifest the wide range of skin disorder, classification, clinical features and management etc. Due to modified life style, lack of physical exercise, mental stress, over eating, nutrition deficiency skin diseases are commonly observed. In worldwide, there is 1/3 leprosy cases found in India. WHO and govt. of India have also run various programs to prevent this, the National Leprosy control program was dispatched by the Govt. of India in 1955. It can be treated in the early stage by using of herbs, Ayurvedic formulations, detoxification process (panchkarma) etc.